2017
DOI: 10.1111/mcn.12544
|View full text |Cite
|
Sign up to set email alerts
|

Babies in boxes and the missing links on safe sleep: Human evolution and cultural revolution

Abstract: Concerns about bedsharing as a risk for sudden infant death syndrome and other forms of sleep-associated infant death have gained prominence as a public health issue. Cardboard "baby boxes" are increasingly promoted to prevent infant death through separate sleep, despite no proof of efficacy. However, baby boxes disrupt "breastsleeping" (breastfeeding with co-sleeping) and may undermine breastfeeding. Recommendations enforcing separate sleep are based on 20th century Euro-American social norms for solitary inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(51 citation statements)
references
References 56 publications
1
50
0
Order By: Relevance
“…Throughout the article, for clarity, I will refer to all of these practices under the heading of ' co-sleeping' in that they are all framed as alternatives to sleep-training, involve parental responsiveness to infants at night, and do not involved early independence training. of attachment also supports many of the claims made by co-sleeping advocates, who are able to cite studies indicating that infants left alone have elevated stress hormones even after they learn not to cry (Middlemiss, Granger, & Nathans 2012) and that over time, that this may impair brain development (Bartick et al 2017) as a result of 'toxic stress' (Shonkoff et al 2012). Sleep training practices are based on theories of behaviour modification (Hiscock & Fisher 2015).…”
Section: Introductionmentioning
confidence: 52%
See 2 more Smart Citations
“…Throughout the article, for clarity, I will refer to all of these practices under the heading of ' co-sleeping' in that they are all framed as alternatives to sleep-training, involve parental responsiveness to infants at night, and do not involved early independence training. of attachment also supports many of the claims made by co-sleeping advocates, who are able to cite studies indicating that infants left alone have elevated stress hormones even after they learn not to cry (Middlemiss, Granger, & Nathans 2012) and that over time, that this may impair brain development (Bartick et al 2017) as a result of 'toxic stress' (Shonkoff et al 2012). Sleep training practices are based on theories of behaviour modification (Hiscock & Fisher 2015).…”
Section: Introductionmentioning
confidence: 52%
“…The opportunity to stay home is most commonly provided by wage-earning partners. Practicing co-sleeping requires the maintenance of a breastfeeding relationship as it is considered unsafe for nonbreastfeeding parents to co-sleep (Bartick et al 2017). The continuation of breastfeeding itself can be understood as an economic privilege.…”
Section: The Care Deficit and Baby Sleep Anxietymentioning
confidence: 99%
See 1 more Smart Citation
“…102 One observational study has shown that, compared with mothers who room-shared without bedsharing, mothers who bedshared were more likely to report exclusive breastfeeding (adjusted odds ratio [OR]: 2.46; 95% confidence interval [CI]: 1.76-3.45) or partial breastfeeding (adjusted OR: 1.75; 95% CI: 1.33-2.31). 7,103 Therefore, advice to avoid bedsharing has the potential to undermine breastfeeding goals, 3,8,104,105 and may increase risk of sleeping in unsafe environments such as sofas. 106 Although mothers and infants can sleep apart and still breastfeed exclusively, doing so results in fewer sessions of breastfeeding per night: bedsharers have double or triple the number of breastfeeding sessions and total amount of breastfeeding time compared with solitary sleepers.…”
Section: History Context and Anthropology Of Infant Sleep Locationmentioning
confidence: 99%
“…Results from case-control studies internationally form the basis for infant sleep recommendations. We are, therefore, concerned that cardboard boxes are being promoted for infant sleep, as a safe alternative to the more traditional cots, bassinets, or Moses baskets, without any observational evidence in place 23. The cardboard baby box is based on a Finnish tradition of giving pregnant women a box full of free infant care items—including a mattress that fits into the bottom of the box as a makeshift infant sleeping environment—as an incentive to enter prenatal care early.…”
mentioning
confidence: 99%